A systematic review of the role of teachers’ support in promoting socially shared regulatory strategies for learning - Sulla, Francesco; Monacis, Domenico; Limone, Pierpaolo (Frontiers in psychology, 2023)
Interpersonal physiological synchrony and collaboration in educational contexts have been identified as key aspects of the learning environment to foster critical thinking, decision-making, problem-solving, and shared knowledge construction and learning of students. In addition to this, teachers’ support and interaction with students result in a protective factor for students’ well-being and academic outcomes. The main aim of this systematic review was to explore if and how teachers’ support and relationship with students can affect their use of Socially Shared Regulatory Strategies for Learning (SSRL). Studies were identified in six electronic databases (Web of Science, Scopus, PubMed, Embase, and Cochrane CENTRAL and ERIC) following PRISMA guidelines. The initial search yielded a total of 110 records. Fifty-nine studies were fully reviewed, and 16 studies met all inclusion criteria and formed the basis for the review. Studies were analyzed and teachers’ support strategies to enhance SSRL were identified and recorded. This review identifies a range of teachers’ strategies that may foster students’ SSRL, such as prompting and moving from one group to another, helping and checking the groups’ progress, especially in primary and secondary school; flipped classrooms at university level. The results of this systematic review may inform teachers, educational practitioners, the general public and the design of individualized educational interventions aimed at improving teacher-child relationships, their well-being and academic performance.